Keadilan Sosial dalam Ekonomi Platform Digital dan Tantangan Etika Ketenagakerjaan - Ilham, Nila Rusyandi; Hanifah, Pitria; Fitratullah, Roni (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The digital platform economy has become a central pillar of the transformation of the global labor market. This model offers efficiency and flexibility, yet it also raises serious concerns regarding social justice and labor ethics. This study aims to critically examine how social justice is positioned within the digital platform economy and to identify the ethical labor challenges faced by platform workers. The research employs an interdisciplinary normative legal approach that integrates labor law analysis, ethical inquiry, and social justice theory. The methods include conceptual, statutory, and comparative approaches, supported by a critical analysis of platform labor contracts and algorithmic management practices. The findings indicate that the platform economy creates asymmetric employment relations in which workers occupy a subordinate position without formal recognition as employees. The flexibility promoted by platforms is often illusory, as it is constrained by strict algorithmic control. This situation generates deficits in procedural and distributive justice and weakens the protection of workers’ fundamental rights. From an ethical perspective, low levels of transparency, accountability, and corporate social responsibility further intensify worker vulnerability. This study concludes that achieving social justice in the platform economy requires adaptive regulatory reform, a stronger role of the state, and the internalization of ethical and justice principles within platform business models. Such an integrated approach is essential for the development of a fair and sustainable digital economy.